The determinants of Global Account Management (GAM). A relationship decision-making model - Deszczyński, Bartosz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
The article presents an analysis of the factors influencing the partnership and cooperation of companies active in the global B2B market. It outlines the benefits that are traditionally associated with joint projects or alliances and discusses to what extent they can be generated in the global customer relationship management programs on the basis of global account management (GAM). The main aim of this paper is to propose a GAM relationship decision-making model. Its conceptual framework is based on four assumptions dealing with the formal and informal, external and internal decision-making factors. This model can be of practical importance for globally operating suppliers in managing their relations and choosing the right customers for strategic cooperation
Argumenta Oeconomica, 2019, Nr 2 (43), s. 233-253
Keywords: cooperation; relationship management; Global Account Management (GAM); partnership